2018
DOI: 10.5007/1980-0037.2018v20n2p182
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of both sex marathon runners ranked by IAAF

Abstract: Running a marathon has become the motivation to achieve success and economic independence for athletes, mainly from African countries. This feeling is more evident among the black community, considering that they have been presenting better results than white athletes. The objective of the study was to analyse the ranking of marathon runners around the world, in the last 15 years considering: 1) nationality; 2) best average time of the 100 best classified runners from the Top 100, Top 50, Top 25, Top 10 and To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Similar results were also observed among female runners, but with a slight difference. These findings can explain results in the present study, where no statistically significant difference was observed in the age of peak performance between sexes when considered athletes in the top 3, given that, for both sexes, this group may be majority composed by African athletes, which may have similar age, regardless of the sex [ 31 ].…”
Section: Discussionsupporting
confidence: 53%
“…Similar results were also observed among female runners, but with a slight difference. These findings can explain results in the present study, where no statistically significant difference was observed in the age of peak performance between sexes when considered athletes in the top 3, given that, for both sexes, this group may be majority composed by African athletes, which may have similar age, regardless of the sex [ 31 ].…”
Section: Discussionsupporting
confidence: 53%